(untitled) (Third Sector Social Economic Review, 2025)
This study aims to reveal the fundamental structure of the academic literature on Central Bank Digital Currencies(CBDCs) by conducting a bibliometric analysis of the 343 publications. Using the keywords Central Bank Digital Currency and CBDC, studies published between 2018 and 2024 were obtained from the Web of Science database. The analysis and visualization processes were carried out using the VOSviewer. The findings indicate a remarkable increase in academic interest in CBDCs, with a concentration of publications originating from China, the United States, and European countries. Keyword co-occurrence and density analyses demonstrate that CBDCs constitute a multidisciplinary research domain that intersects not only with monetary innovation but also with areas such as blockchain, cybersecurity, data-privacy, and regulatory frameworks. Citation, author, and country network analyses reveal an increasingly integrated intellectual structure, a rise in international collaborations, and a deepening of research at a global scale. The study emphasizes the need to address CBDCs from technological, financial, and geopolitical perspectives. By highlighting thematic trends, conceptual gaps, and fundamental issues in the literature, it aims to provide a strategic perspective on the rise of digital currencies. This study seeks not only to contribute to academic discussions but also to benefit central banks, policymakers, market regulators and all relevant stakeholders.